P–152 Morphokinetic and maternal profiles of embryos derived from centrally granulated oocytes vary with their ability to implant. (6th August 2021) - Moutier, C; Bartolacci, A; Turchi, D; Lain, M; Pignataro, D; Mignin. Renzini, M R; Buratini, J; Da. Canto, M
Abstract: Study question: Does oocyte central granularity (CG) impact embryo morphokinetics and does this change with embryo implantation ability and maternal profile? Summary answer: Oocyte CG slows fertilization and cleavage morphokinetics in overall derived embryos, but not in those capable to implant, an ability associated with lower maternal age. What is known already: Oocyte morphology is easily accessible after pre-ICSI oocyte denudation, but the implications of morphological alterations for oocyte developmental competence are not entirely known. The presence of a centrally located granular area in the ooplasm was previously associated with alterations in the actin cytoskeleton and meiotic spindle, both potentially affecting meiosis completion, fertilization dynamics and embryo mitotic divisions. In fact, we have recently reported lower fertilization rates and delayed pronuclei fading and first cleavage associated with the presence of CG in oocytes subjected to ICSI. Study design, size, duration: Retrospective analysis including 1378 control ICSI cycles providing only morphologically normal oocytes (1225 patients) and 220 CG cycles (201 patients) providing normal and CG oocytes, from July 2014 to March 2020. Morphokinetic parameters were compared between embryos from control and CG oocytes, as well as among embryos from control oocytes reaching implantation (C-I) and embryos from CG oocytes achieving (CG-I) or not (CG-NI) implantation. Maternal profiles were compared between CG-I and CG-NI. Participants/materials, setting, methods: Oocytes were recovered from patients after controlled ovarian stimulation and ovum pick-up. Following ICSI, embryo culture was performed in a time-lapse incubator with annotation of time of pronuclei fading (tPNf) and cleavage times t2, t3, t4, t5 and t8. Morphokinetic data were retrospectively coupled with implantation outcomes of single transfers and of double transfers achieving double or no implantation. Differences were assessed with Chi-square and Kruskal Wallis tests. Main results and the role of chance: Patients providing CG oocytes (n = 201) presented higher maternal age (37.4 ± 4.4 vs. 36.7 ± 4.3; p = 0.005), higher basal FSH (8.52 ± 3.7 vs. 7.62 ± 2.8 IU/L; p = 0.002) and lower AMH levels (2.2 ± 2.2 vs. 2.9 ± 3.1 ng/mL; p < 0.001) compared to control patients (n = 1225). Morphokinetic parameters from tPNf to t4 were faster in embryos derived from oocytes with normal morphology (control; n = 6947) compared to embryos derived from CG oocytes (n = 382; tPNf: 24.0 ± 3.8 vs. 24.6 ± 3.6; t2: 27.0 ± 4.3 vs. 27.6 ± 4.1; t3: 37.0 ± 5.7 vs. 37.4 ± 5.7; t4: 39.4 ± 6.4 vs. 40.1 ± 6.2 hours; p < 0.05). In addition, CG-NI (n = 103) embryos were slower than CG-I (n = 13) and C-I (n = 226) embryos for tPNf, t2, t3, t4 and t8 (p < 0.05), while CG-I did not differ from C-I embryos (p > 0.05; tPNf: 22.4 ± 2.6 vs. 22.0 ± 2.5; t2: 24.9 ± 2.7 vs. 24.6 ± 2.8; t3: 36.0 ± 3.5 vs. 35.4 ± 3.0; t4: 36.7 ± 3.5 vs. 36.7 ± 3.6 hours, for C-I and CG-I, respectively). Finally, patients providing CG-I embryos (n = 10) were younger than those providing CG-NI embryos (n = 65; 31.3 ± 4.6 vs. 38.0 ± 3.9; p < 0.05). Limitations, reasons for caution: Our study is subjected to the intrinsic limitations of a retrospective analysis, the results presented could have been affected by variables that are uncontrolled for. Other studies are necessary to assess the impact of CG on clinical outcomes. Wider implications of the findings: The findings indicate that early developmental morphokinetics and maternal age constitute valid parameters for the decision of whether to transfer CG-derived embryos, as well as for the transfer prognosis. Trial registration number: Not applicable